(untitled) (Eurasian Journal of Philology Science and Education, 2018)
The article deals with the concepts of MARRIAGE and FAMILY in the Kazakh and English languages. The study of these concepts is of interest because they are basic in the system of social relations, and largely determine the functioning of society, and the institution of marriage and family is one of the integral elements of culture. In the course of the research, various definitions of the notion of “concept” have been considered, including those given from the position of linguoculturology, the significance of which is due to the expansion of international relations and globalization and the need to take into account the specific features of culture and language of different nations. The linguocultural aspect of the research can help to identify the universal and national-specific features of these concepts, which is to a large extent explained by their ability to reflect and fix in the language the manifestations of the culture of a particular nation.